2005
DOI: 10.1007/s10554-005-9005-3
|View full text |Cite
|
Sign up to set email alerts
|

The anomalous origin of the left coronary artery from the right aortic sinus: is the coronary angiography still a ‘gold standard’?

Abstract: Coronary artery anomalies remain a poorly understood topic in modern cardiology. The most important issue is the origin of the left coronary artery or the left anterior descending artery from the opposite aortic sinus, frequently associated with sudden cardiac death. We report our experience concerning the evaluation of these anomalies. From 15 April 1997 to 1 December 2004, we performed 13.407 coronary angiographies and found eight patients with these anomalies. In seven patients the coronary angiography was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 8 publications
0
19
0
1
Order By: Relevance
“…The base of diagnosis is centred in a thorough study of coronary arteries by such imaging techniques. It is important to highlight that among the invasive methods, the coronary angiography, considered before as a "gold standard" in cases of anomalies of coronary arteries, now has been replaced by modern imaging techniques such as multislice computered tomography or magnetic resonance that show us the images in three dimensions [7] .…”
Section: Discussionmentioning
confidence: 99%
“…The base of diagnosis is centred in a thorough study of coronary arteries by such imaging techniques. It is important to highlight that among the invasive methods, the coronary angiography, considered before as a "gold standard" in cases of anomalies of coronary arteries, now has been replaced by modern imaging techniques such as multislice computered tomography or magnetic resonance that show us the images in three dimensions [7] .…”
Section: Discussionmentioning
confidence: 99%
“…3,6 In reviewing the medical literature, we found rare cases of anomalous origin of the LMCA from the right coronary cusp. [3][4][5][6][7][8] Most reports concern the anomalous origin of the right coronary artery. To the best of our knowledge, no reported case is similar to ours in regard to clinical presentation and the presence of an unusually long intramural course of the LMCA between the aortic root and the PA trunk.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, initial experience have already shown that DSCT permits imaging of the coronary arteries in a substantially increased number of patients compared to earlier scanner generations [12]. Thus, as suggested recently, it seems to be questionable whether coronary angiography is still a gold standard in the examination of patients with coronary anomalies [13][14][15]. On the other hand, the catheterization technique is still indispensable for endovascular treatment of these patients.…”
Section: Discussionmentioning
confidence: 99%